Moral Contextualism and the Problem of Triviality - Evers, Daan (Ethical theory and moral practice, 2014)
Moral contextualism is the view that claims like ‘A ought to X’ are implicitly relative to some (contextually variable) standard. This leads to a problem: what are fundamental moral claims like ‘You ought to maximize happiness’ relative to? If this claim is relative to a utilitarian standard, then its truth conditions are trivial: ‘Relative to utilitarianism, you ought to maximize happiness’. But it certainly doesn’t seem trivial that you ought to maximize happiness (utilitarianism is a highly controversial position). Some people believe this problem is a reason to prefer a realist or error theoretic semantics of morals. I argue two things: first, that plausible versions of all these theories are afflicted by the problem equally, and second, that any solution available to the realist and error theorist is also available to the contextualist. So the problem of triviality does not favour noncontextualist views of moral language.